Forest products and local forest management in West Kalimantan, Indonesia: implications for conservation and development - Jong, W. de (Tropenbos International, 2002)
This book critically investigates the proposition that commercialisation of forest products contribute to both enhancing people's income and to conservation of tropical forests, using evidence from a case study from West Kalimantan, Indonesia. It draws the main conclusion that promoting commercialisation of forest products often leads to a shift of the dominance of this trade by outside entrepreneurs. Even where local people manage to control the trade, the conservation impact on tropical forests is only indirect. By studying detailed examples of local forest management in three indigenous villages in West Kalimantan, Indonesia, this book concludes that the conservation of tropical forests through forest products commercialisation is most likely to happen when local producers shift to active management of forest products in anthropogenic forests. The long term impact of such local forest management depends importantly on how local or regional economies develop. Land use intensification may take place on some parts in the landscape, where previously intensively managed forests may be left to themselves.